Diversity and Abundance of Epiphytic Diatoms on Seagrass Leaves (Enhalus acoroides) in Poncan Gadang Island Sibolga City, North Sumatra - Dinda Trie K Hayati; Sofyan Husein Siregar; Rifardi Rifardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The seagrass ecosystem is one of the marine ecosystems that has an important role, namely as a source of life for organisms in the sea. Diatoms are microalgae widely distributed throughout the aquatic environment and are even found in plants, including seagrass leaves. Diatoms greatly influence life in the waters because they play an essential role as a food source for various marine organisms and play a role in the transfer of carbon, nitrogen, and phosphate. This research was conducted in February 2023 on Poncan Gadang Island, Sibolga City, North Sumatra. The study aims to determine the density, relative abundance, abundance, and diversity of epiphytic diatom species on seagrass (Enhalus acoroides) leaves in Poncan Gadang Island. The method used is the survey method, using three stations to take samples. The determination of 3 stations is based on the density of the seagrass beds ecosystem. Sampling of diatoms was carried out by brushing the surface of seagrass leaves about 5x2 cm on the front and back of the leaves. The samples obtained were then analyzed in the laboratory. There were 12 types of diatoms found, consisting of Cocconeis sp., Rhizosolenia sp., Biddulphia sp., Amphipluera sp., Thalassiotrix sp., Nitzchia sp., Synedra sp., Melosira sp., Pleurogosigma sp., Skeletonema sp., Licmiphora sp., and Thalassionema sp. the average value of epiphytic diatom abundance in seagrass leaves ranged from 2160.85 – 4649.94 ind/cm². The epiphytic diatom diversity (H') values ranged from 2.53 to 2.72